The Urgence of Strengthening Family Resistance Arrangements - Hanin Ramadhanti; Noor Fatimah Mediawati (Indonesian Journal of Law and Economics Review, 2021)
This study aims to determine and examine the urgency of strengthening the regulations governing family resilience in Sidoarjo Regency. The research method used is normative by using the Law approach and the Conceptual approach which is carried out by analyzing various regulations. Data is collected through primary data collection from legislation and secondary data from law books and several legal journals that are related to the topic under study. Divorce can occur due to several things so that it can be a reason for a divorce application to the Court. From this study it can be concluded that in Sidoarjo Regency there are regulations regarding family resilience in the form of regulations under the auspices of the Ministry of Religion which are not mandatory. Furthermore, with the facts listed, Sidoarjo Regency has experienced an increase in the divorce rate every year as a result of not being obliged to follow these rules. So it is very necessary for Sidoarjo Regency to establish rules regarding family resilience by the Regional Government which are mandatory so that there is no increase in the divorce rate every year.